Object-Based Analysis/Synthesis Audio Coder for Very Low Bit Rates - Purnhagen, Heiko; Edler, Bernd; Ferekidis, Charalampos (104th AES Convention, 1998)
An Object-Based Analysis/Synthesis Audio Coder designed for bit rates between 4 and 16 kbit/s is presented. The coding is based on the decomposition of the input signal into audio objects which are described by appropriate source models and represented by model parameters. Object models for sinusoids, harmonic tones, and noise are utilized. <p